2009
DOI: 10.1080/11038120802409747
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal changes in everyday life after home modifications for people aging with disabilities

Abstract: Home modifications are effective in decreasing difficulty in performing everyday life tasks up to six months after the installation. Furthermore, to be effective home modifications need to be installed in a timely fashion. For each consecutive month the person waited for their home modification the difficulty of performing everyday life tasks increased. Therefore, it is important that home modifications be installed as soon as possible after the need has been identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
60
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 18 publications
8
60
0
Order By: Relevance
“…The longitudinal findings of this study show that in a relatively short period of time the health and caring situation can change, also putting the HA into another light, thus the HA was seen as a piece of the puzzle. Encouraging people with disabilities to apply earlier in the process and also to reduce the time between application and installation [17] would possibly make it easier for people to make use of the HA and actually reach the goals of independence and safety [30].…”
Section: Housing Decisionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The longitudinal findings of this study show that in a relatively short period of time the health and caring situation can change, also putting the HA into another light, thus the HA was seen as a piece of the puzzle. Encouraging people with disabilities to apply earlier in the process and also to reduce the time between application and installation [17] would possibly make it easier for people to make use of the HA and actually reach the goals of independence and safety [30].…”
Section: Housing Decisionsmentioning
confidence: 99%
“…Several positive outcomes of home modifications and HAs for the client have been demonstrated, e.g. in relation to falls [12][13][14], usability [15,16] and activity [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic overview of studies targeting outcomes of housing adaptations (6), substantial evidence of reduced disability, for example dependence in ADL and IADL, was found in some studies, (3,5,(7)(8)(9)(10)(11)(12) but other studies (13)(14)(15) indicated that the intervention had no such effects. Instead, multidimensional interventions comprising a variety of strategies, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Housing adaptation is a common compensatory intervention used by occupational therapists to enhance independent living (1)(2)(3)(4)(5), to increase usability in the home and to support activity and participation. In a housing adaptation, the physical home environment is altered, and the intervention is individually tailored in order to meet the specific needs of the person in the home.…”
Section: Introductionmentioning
confidence: 99%
“…shower chair, movement sensors) (Pynoos et al 2003;Sanford 2012); others explained it as an alternation to the physical environment (e.g. replacement of a bath, installation of a ramp) that enables an individual with a functional limitation to perform everyday activities at home (Johansson et al 2007;Petersson et al 2009). In this study, housing adaptation refers to modifications of permanent physical features in the indoor and immediate outdoor environment to reduce environmental barriers and restore independent living.…”
Section: Introductionmentioning
confidence: 99%